Mesenteric fat thickness is associated with metabolic syndrome independently of Apnoea–Hypopnoea Index in subjects with obstructive sleep apnoea. Issue 3 (21st December 2015) - Liu, Kin Hung; Chu, Winnie C.W.; To, Kin Wang; Ko, Fanny W.S.; Ng, Susanna S.S.; Ngai, Jenny C.L.; Chan, Ka Pang; Yip, Wing Ho; Ahuja, Anil T.; Hui, David S.C.
Abstract : The two ultrasound images present mesenteric fat leaves in study subjects with mild (left) and severe (right) obstructive sleep apnoea (OSA). The single‐head arrows point to peritoneal surfaces in both images. The longer double‐headed arrow in the right image reflects a greater distance between two peritoneal layers in mesenteric fat of subjects with severe compared to mild OSA. Abstract: Background and objective: Mesenteric fat thickness (MFT) was associated with metabolic syndrome (MetS) and obstructive sleep apnoea (OSA) in separate studies. This study aimed to assess whether the association of MFT with MetS was independent of OSA in subjects with suspected OSA. Methods: Two hundred forty‐two subjects (men: 181; women: 61) with suspected OSA underwent ultrasound examinations for measurements of mesenteric, subcutaneous and preperitoneal fat thicknesses after overnight polysomnography. Anthropometric measurements and metabolic risk profile were assessed. Results: Two hundred twenty‐one (91%) subjects were confirmed to have OSA with Apnoea–Hypopnoea Index (AHI) >5/h. MFT had significant correlation ( P  < 0.01) with AHI and most MetS components. In partial correlation with adjustment for AHI, MFT had significant correlation ( P  < 0.01) with most MetS components including fasting plasma glucose (r = 0.25), triglycerides (r = 0.24), HDL cholesterol (r = −0.29) and waist circumference (r = 0.56). In multivariate logistic regression with adjustments for the confounding variables including AHI, MFT was the only variable independently associated with MetS, with the odds ratio of 5.48 (95% CI: 1.5–20.0) for every 1 cm increase of MFT. When the subjects were subdivided into obese (BMI ≥ 27.5 kg/m 2 ) and non‐obese (BMI < 27.5 kg/m 2 ) groups, the positive association of MFT with MetS persisted in the non‐obese group only, with the odds ratio of 22 (95% CI 2.8–174.1) for every 1 cm increase of MFT. The AHI had significant association with MetS in male subjects only. Conclusion: MFT, rather than AHI, is the major independent determinant of MetS in subjects with suspected OSA, particularly in non‐obese subjects. See Editorial, page 408